Self-regulated learning and problem-solving ability of elementary school students in fraction during online learning - Eva Yunida Wulandari; Fitri Alyani (Jurnal Elemen, 2022)
Online learning for students requires high self-regulated learning to maximize problem-solving skills, especially in fractional material. However, elementary school students have not widely seen self-regulated learning and problem-solving abilities. Therefore, this study aimed to determine the relationship between self-regulated learning and problem-solving skills, especially on fractions in online learning in fifth-grade elementary school. This research is included in a quantitative study that uses a sample of fifth-grade students in an elementary school in Depok City. A sample of 122 students (N = 67 female, N = 55 male) was obtained using a non-probability sampling technique. Data collection techniques were carried out through the distribution of a self-regulated learning questionnaire with as many as 29 statements and a problem-solving ability test instrument with as many as eight questions. The data obtained were measured and analyzed using Rasch modeling and assisted by Winsteps software version 4.4.2. Furthermore, the correlation and Effect Size tests were carried out to determine the relationship and influence between variables. The results showed a significant and interrelated relationship between self-regulated learning and problem-solving ability. In other words, the higher the quality of independence in students, the higher the quality of problem-solving abilities they have, and vice versa. That way, it can encourage students to maximize self-regulated learning when learning online to help improve problem-solving skills in learning.